The Effect Of Third Party Financing And Funds On Total Assets In Sharia Financing Banks In Indonesia 2016-2020 Period - Arfa Syera, Inda; Affiah, Hajar (Publisher Cv. Inara, 2022)
The specific purpose of this study is to determine the effect of Financing and Third Party Funds on the Total Assets of Islamic People's Financing Banks. The approach used in this research is a quantitative approach. The data used in the form of secondary data from the website of the Financial Services Authority (OJK). The population is monthly data from January 2016 to December 2020 period while the sample is annual data from 2016 to 2020. The research analysis carried out is multiple linear regression, classical assumption test (normality test, heteroscedasticity multicollinearity test and autocorrelation test), and test statistics (coefficient of determination (R2), statistical F test, and statistical t test). The results of this study are the variables of Financing and Third Party Funds have a significant effect simultaneously (simultaneously) on the variable Total Assets of Islamic People's Financing Banks.